REAKTUALISASI NILAI-NILAI ISLAM KLASIK DI ERA GLOBAL (Telaah atas Visi Misi IAIN Palu) - Moh. Ali (ISTIQRA, 2017)
Classical Islam is a symbol and a reflection of the thought of the ancient clerics who contributed positions and solutions in the life of a nation and religion, so that life would be safe, peaceful, loving, just and democratic without oppressing each other. And people who learn classical Islam will have extraordinary personality, because it is a consequence of a Muslim's faith, which must have two fundamental aspects, namely the mindset ('aqliyyah) and the pattern of the soul (nafsiyyah) based on the classical Islamic aqidah. And to develop a classical Islamic personality there are three steps that must be taken, as exemplified by the Prophet, namely: first Inculcating aqidah Islam. Second Inculcate consistent attitude and istiqâmah in people who already have aqidah of Islam so that way of thinking and berprilakunya remain on the foundation of aqidah which is believed. When Develop the personality of Islam that has been formed on someone by always invites him to earnestly fill his thoughts with tsaqâfah islâmiyyah and obedient to Allah SWT